ESOPHAGEAL PATHOPHYSIOLOGICAL DISORDERS IN PATIENTS WITH POST SLEEVE GASTRECTOMY - Hussein, Khalid Khairi (Eastern Ukrainian Medical Journal, 2026)
Introduction and Aim: Sleeve gastrectomy (SG) is currently the most popular bariatric procedure around the world because it is effective and has good long-term results. The purpose of this study was to determine the prevalence, severity and risk factors of GERD in patients who have undergone SG and the effect of preoperative conditions and weight loss following surgery on these outcomes. Materials and Methods: This was a retrospective cohort study which was conducted in a single institution and the patients involved were one hundred who underwent SG between the 1st of November 2023 and June 2024 and had follow up of 1.5 years. The age of the patient had to be ≥18 years, on preoperative characteristics and postoperative complications and esophageal symptoms using the GERD-HRQL (Health Related Quality of Life) scale. Results: The mean age of the patients was 45.2 ± 10.3 years, with a mean preoperative BMI of 42.5 kg/m². Preoperative GERD was present in 30% of the patients. Postoperatively, 16% developed GERD, with 18% experiencing some form of esophageal symptom, including dysphagia (4%), heartburn (3%), and regurgitation (2%). Preoperative GERD was the most significant predictor of postoperative GERD, with patients nine times more likely to experience symptoms (OR 9.2, p < 0.001). Conclusions: Postoperative GERD is a common complication after SG, particularly in patients with preoperative GERD, high BMI, and older age. Monitoring and managing GERD symptoms, especially in high-risk patients, is crucial for improving postoperative outcomes.